Voice Security Using Hybrid Algorithm - Alyaa Abdul Majeed Haleem (Al-Rafidain Journal of Computer Sciences and Mathematics, 2010)
This research deals with constructing and implementing a new digital voice security Algorithm based on hiding large amount of data (sound file) in a 24 bits host color image (RGB image). The proposed method starts with speech compression to convert human speech into an efficiently encoded representation that can later be decoded to produce a close approximation of the original signal. The process of compression is achieved by first computing Discrete Wavelet Transform (DWT), truncating small-valued coefficients and then efficiently encoding them. The stream bits output from coder are encrypted using Linear Feedback Shift Register (LFSR) algorithm. These enciphered bits are then embedded into the image blocks. A binary key matrix and weight matrix are used as a secret key to protect the hidden information. The algorithm can hide as many as  bits of data in the image by changing one bit in each block of size . High security algorithm was achieved using three layers to make it difficult to break by attacker. The algorithm has been implemented using MATLAB.